PENINGKATAN PEMBELAJARAN KREATIF MELALUI PENGENALAN DAN PENGADAAN PEMBUATAN ALAT PERMAINAN EDUKATIF BAGI GURU PAUD - Gunawan, Maya Regita; Ekasari, Agustina; Rahmawati, Rafika (Universitas Islam 45 Bekasi, 2023)
APE is a game tool designed and created to be a learning resource for young children to gain learning experience. And this experience is very useful in improving aspects of children's development, both physical (motor), emotional, social, language, cognitive and moral. This program for introducing and procuring educational game equipment (APE) aims to provide insight and knowledge about APE for early childhood teachers in Sumberreja Village. This activity was carried out in the form of introducing and providing educational game equipment (APE) for teachers. The target participants for this program are TKA Miftahul Huda pre-school teachers, totaling 2 people. This activity lasted for two and a half hours. The conclusion is that the introduction and provision of APE production has had a positive impact on early childhood teachers themselves, namely that they can increase their knowledge and insight regarding APE for early childhood. And you can also tell preschool teachers about teaching materials that are easy to make, and suitable for children whose development is less than that of children their age and young children who get bored easily when learning. And it can also increase children's interest in learning because APE is very interesting for young children.